Respon cepat pasar modal (LQ 45) terhadap pandemi Covid-19 - Oktavia, Irma; Sitinjak, Norman Duma (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2022)
This study examines investor responses to stocks listed on the IDX's LQ 45 index before and during the early days of the Covid-19 pandemic. The sample selected based on purposive sampling was 39 companies. The event period is 7 stock trading days, namely 3 days before, and 3 days after the Covid 19 pandemic. The results show that the Covid 19 pandemic event is bad news information for investors, so the stock value before and at the beginning of the Covid 19 pandemic is different. The difference was caused by the declining share value. Trading transactions also experienced differences, namely an increase in transactions, the majority of which were selling actions to avoid bigger losses.